2021
DOI: 10.1186/s12879-021-06356-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of two-week therapy with doxycycline-based quadruple regimen versus levofloxacin concomitant regimen for helicobacter pylori infection: a prospective single-center randomized controlled trial

Abstract: Background Antibiotic-resistance reduces the efficacy of conventional triple therapy for Helicobacter Pylori infections worldwide, which necessitates using various treatment protocols. We used two protocols, doxycycline-based quadruple regimen and concomitant levofloxacin regimen. The aim was to assess the effectiveness of doxycycline-based quadruple regimen for treating Helicobacter Pylori infections compared with levofloxacin concomitant regimen as empirical first-line therapy based on intent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…[35] While the doxycycline-based quadruple regimen and levofloxacin concomitant regimen was effective in 82% of cases. [36] When reviewing patient charts, it was found that there is a significant flaw in documenting the H. pylori infection status, treatment protocol, and treatment result. Although there is a clear policy regarding the medical file, including the results of tests and biopsies, this policy is not always followed because the Syrian health sector is facing severe challenges due to doctor emigration, a shortage of nursing staff, and imposed sanctions.…”
Section: Discussionmentioning
confidence: 99%
“…[35] While the doxycycline-based quadruple regimen and levofloxacin concomitant regimen was effective in 82% of cases. [36] When reviewing patient charts, it was found that there is a significant flaw in documenting the H. pylori infection status, treatment protocol, and treatment result. Although there is a clear policy regarding the medical file, including the results of tests and biopsies, this policy is not always followed because the Syrian health sector is facing severe challenges due to doctor emigration, a shortage of nursing staff, and imposed sanctions.…”
Section: Discussionmentioning
confidence: 99%
“…Other risk factors are genetic and family history of cancers such as hereditary nonpolyposis colorectal cancer (Lynch syndromes I & II) and familial adenomatous polyposis (FAP) [ 7 ], and none of them appear to be true in our case based on the history. Helicobacter Pylori infection is the most potently recognized risk factor for gastric adenocarcinoma; however, even after decades of infection, the only an insignificant proportion of infected subjects develop adenocarcinoma [ 8 ], and there is insufficient evidence to suggest the optimal age to begin eradication therapy [ 9 , 10 ], knowing that Helicobacter pylori infection eradication is difficult in Syria [ 11 , 12 ]. Early detection of a gastric tumor is critical in determining prognosis, and each of the following indicates metastatic gastric cancer: weight loss, anemia, Virchow nodes (left supraclavicular), Irish node (anterior axillary), and periumbilical (Sister Mary Joseph nodule).…”
Section: Discussionmentioning
confidence: 99%
“…For two weeks, patients on the concomitant levofloxacin regimen will receive levofloxacin 500 mg once daily, amoxicillin 1000 mg, tinidazole 500 mg, and esomeprazole 20 mg twice daily. When applied as a first-line treatment, the previous regimen had the highest eradication rate for Syrian patients naive to HP treatment [ 36 , 37 ]. A rescue regimen of high-dose dual therapy consisting of esomeprazole (40 mg twice daily) and amoxicillin (1000 mg three times daily) for 2 weeks will be used after first-line treatment fails [ 22 , 39 ].…”
Section: Methods: Participants Interventions and Outcomesmentioning
confidence: 99%
“…However, the increasing antibiotic resistance of HP has become a major global problem [ 24 35 ]. In Syria, the eradication rate of traditional triple therapy with clarithromycin or levofloxacin was less than 30% [ 36 ], whereas the eradication rate with the levofloxacin concomitant regimen and the doxycycline-bismuth-based quadruple regiment was 82.05% and 78.9%, respectively [ 37 ]. As a result, there is a need to look for more effective therapeutic regimens as well as the best therapeutic regimens for follow-up when the first line of treatment fails.…”
Section: Introductionmentioning
confidence: 99%